Cave Survey in Mining Sector: Advances and new technologies - Fernandes, Adam Barros; Borba, Ricardo Perobelli; Brandi, Iuri Viana; Araújo, Ramon Nunes; dos Santos Scherer, Bruno; Corrêa, Tomás Romualdo; Boulhosa, Gabrieli Santos [UNESP] (Revista Brasileira de Geomorfologia, 2023)
Cave topographic maps are essential data for a series of scientific studies, environmental licensing purposes and the preservation of speleological heritage. However, map sketching follows practically the same methodology in the last 100 years, using three basic equipment: compass, clinometer and tape measure. This paper presents a bibliographic review of the evolution of cave survey methods in mining sector. The types of instruments of cave survey are compared. With regard to the most current topographic surveys, the use of 3D laser scanning and photogrammetry has shown that these methods are promising to improve speleometric parameters (ex: area, volume e horizontal projection), accuracy and achieve greater agility, in view of greater agility to perform field survey, greater ease for interpretation of geological structures, and finaly gaining safety for people on field work.
Mapeamento topográfico de cavernas no setor mineral: Avanços e novas tecnologias
Keywords: Disto X; Laser Scanner 3D; Photogrammetry; Speleology; Topography